ANALISIS EFEKTIVITAS PENYELESAIAN PEMBIAYAAN MUDHARABAH BERMASALAH DI KOPERASI SIMPAN PINJAM SYARIAH SUNGAI ROTAN-BATU TABA - Olivia Rahmatika; Novera Martilova (CV. Adiba Aisha Amira, 2023)
Based on the research results, it shows that there are two solutions to solving this problematic mudharabah financing. Firstly, when financial constraints occur that affect members in paying off financing, the cooperative will provide an extension of time for members to be able to pay off loans. Secondly, KSP Syariah Sungai Rotan- Batu Taba will restructure financing for members who are having difficulty paying loans. This restructuring includes rescheduling payments, adjusting profit sharing or reducing the principal that must be paid. The Sungai-Batu Taba Sharia Savings and Loans Cooperative can be said to have been around 70% effective in resolving problematic mudhrabah financing, which can be seen from the restructuring carried out to help reduce financial burdens which can help members pay off loans that have been made and the annual meeting held in 2021 has reduced the number of members experiencing mudharabah financing problems. Meanwhile, 30% still have communication problems because when contacted, members don't get an answer, so KSP Syariah has difficulty collecting member loans. However, KSP Syariah Sungai Rotan-Batu Taba will still give members time to pay off the loan, but if there is still no answer then the cooperative will come to the member's house